“Getting off the Bus Closer to Your Destination”: Patients’ Views about Pharmacogenetic Testing - Trinidad, Susan Brown (Perm J, 2015)
CONTEXT: Pharmacogenetic testing, a form of precision medicine, has the potential to optimize medication choice and dosing. Yet, relatively little is known about the views of patients—particularly those with chronic psychiatric conditions—with respect to such testing. OBJECTIVE: To explore patients’ beliefs and attitudes regarding pharmacogenetic testing, with the goal of informing policy development and implementation. DESIGN: Qualitative study design using semistructured focus groups with adults enrolled in Group Health Cooperative, a large health maintenance organization in the Pacific Northwest. We conducted focus groups with patients prescribed antidepressants (pilot session plus 2 focus groups, n = 27); patients prescribed carbamazepine (2 focus groups, n = 17); and healthy patients (2 focus groups, n = 17). RESULTS: Although participants understood the potential advantages of pharmacogenetic testing, many felt that the risks (discrimination, stigmatization, physician overreliance on genomic results, and denial of certain medications) may outweigh the benefits. These concerns were shared across groups but were more strongly expressed among participants with chronic mental health diagnoses. CONCLUSION: Clinical implementation of pharmacogenetic testing must address patient concerns about privacy, discrimination, quality of care, and erosion of the physician-patient relationship.